Electrochemical detection of nickel(II) and zinc(II) ions by a dicarboxyl-Calix[4]arene-based sensor (Calix/MPA/Au) through differential pulse voltammetry analysis - Abdul Aziz, Siti Fatimah Nur; Alang Ahmad, Shahrul Ainliah (IWA Publishing, 2023)
Herein, we report a facile approach for constructing a calixarene-based electrochemical heavy metal sensor (Calix/MPA/Au) via a one-pot reaction for the detection of Ni(II) and Zn(II) ions. The surface elemental properties and analytical performance of the Calix/MPA/Au sensor were characterized by X-ray photoelectron spectroscopy (XPS) and differential pulse voltammetry (DPV). Under optimum conditions, the sensor exhibited detection limits of 1.5 and 0.34 mg/L at linear ranges of 2.85–6.65 and 0.13–1.68 mg/L for the Zn(II) and Ni(II) ions, respectively. The developed sensor exhibited a better electrochemical performance in the detection of Zn(II) and Ni(II) ions owing to the favourable host–guest interactions between the hydroxyl groups-functionalized lower rim of dicarboxyl-calix[4]arene and the metal ions. The RSD of the five independent Calix/MPA/Au electrode for Zn(II) and Ni(II) ions was calculated to be 16.3 and 16.1%, respectively. Despite the lower sensitivity of the modified electrode towards Ni(II) ions, this finding proves the high selectivity of the calixarene as a detection probe towards the fitted size of guest ion, hence promising to be assembled and explored as a solid-state based-supramolecular host molecule for tracing metal ions.